The Influence Of Service Quality And Arak Menu On Customer Satisfaction Of Angkringan/Nge-Stop In Denpasar Bali - Firman Sinaga; Firlie Lanovia Amir; Made Widya Paramitha (Institute of Computer Science (IOCS), 2022)
Based on the Central Bureau of Statistics for the Province of Bali in 2020, the number of restaurants is 2,864 restaurants and the Denpasar area has reached 582 restaurants. Each restaurant has a different sales strategy and tries to get as much revenue as possible. From the above data it can be seen that the competition for restaurants/eateries/angkringan in the Denpasar area is very tight, especially in terms of product innovation (menu), food and beverage quality and service quality offered to customers. In an effort to increase customer satisfaction according to needs and desires, it is necessary to prioritize food and beverage quality, service quality in addition, as an effort to increase repurchase. This research is a quantitative study using multiple linear regression analysis and Coefficient of Determination analysis, using the SPSS for Windows version 2.0 program. with the stepwise method. The results of this study are that partially Service Quality has a positive and significant effect on customer satisfaction of Angkringan/Nge-Warung in Denpasar and Menu Arak has a positive and significant effect on customer satisfaction of Angkringan/Nge-Warung in Denpasar.